PENGARUH DISIPLIN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT CIRCLEKA INDONESIA UTAMA CABANG CAKUNG JAKARTA TIMUR - Submission JORAPI; Asep Ilham; Pancagaluh Ratnasih (Journal of Research and Publication Innovation, 2025)
The performance of employees at PT Circleka Cakung Branch, East Jakarta, shows fluctuations that are suspected to be influenced by inconsistent work discipline levels and suboptimal physical work environment conditions. This study aims to determine the positive and significant effect of the discipline variable on employee performance, to determine the positive and significant effect of the physical work environment variable on employee performance, and to determine the positive and significant effect of the discipline and physical work environment variables simultaneously on employee performance at PT Circleka Indonesia Utama South Jakarta Branch. The method used is quantitative with an associative approach. The sample used is a saturated sampling technique consisting of 50 employees. The research results show that: (1) partially, discipline has a positive effect on employee performance, which can be proven by the linear regression test with the regression equation Y = 10.308 + 0.369 X1, leading to a constant value of 10.308. The t-test has a calculated t-value of 1.809 and a 5% distribution table value of 1.67722 with a significance level of 0.000 < 0.05. (2) partially, the work environment has a positive effect on employee performance, which can be proven by the linear regression test with the regression equation Y = 10.308 + 0.409 X2, leading to a constant value of 10.308. The t-test has a calculated t-value of 1.807 and a 5% distribution table value of 1.67722, so the calculated t-value of 1.807 > the table value of 1.67722 with a significance level of 0.000 < 0.05. This means the work environment has a positive effect on employee performance. (3) Simultaneously, there is a positive and significant influence between motivation and work environment on employee performance at PT. Circleka Indonesia Utama, which can be proven by the multiple linear regression equation Y= 10.308 + 0.369 X1 + 0.409 X2, a correlation value of 0.593, a coefficient of determination value of 59.3%, and an F-value of 10.308 > F-table 3.195 with a significance level of 0.000 < 0.05.